Utility of Baroreflex Sensitivity as a Marker of Stress. (June 2016) - Anderson, Amanda A.; Keren, Nir; Lilja, Andrew; Godby, Kevin M.; Gilbert, Stephen B.; Franke, Warren D.
Presently, adaptive systems use various cognitive and cardiovascular measures to evaluate the functional state of the operator. One marker that has been largely ignored as an assessment tool is baroreflex sensitivity (BRS). This study examined the extent to which BRS changed in response to acute psychological and physical stressors. A total of 20 participants underwent 6-min exposures to a psychological stressor and a physical stressor. Baroreceptor sensitivity, blood pressure, heart rate, heart rate variability, stroke volume, cardiac output, mean blood pressure, total peripheral resistance, left ventricular ejection time, and pre-ejection period were continuously measured at rest and throughout the testing period. Compared to rest, BRS significantly decreased during both the psychological and physical stressors. BRS was reduced more with the psychological stressor than the physical stressor. Heart rate and systolic blood pressure significantly increased above rest during the psychological stressor but not during the physical stressor. There were no significant differences from rest or between stressors for the other physiological markers. BRS was more robustly responsive than other cardiovascular measures commonly used to assess the psychophysiological response to stress, suggesting BRS is a useful marker for evaluating operator functional state during psychological and physical tasks.